Is it possible to find a bifactor structure in the Fear of COVID-19 Scale (FCV-19S)? Psychometric evidence in an Ecuadorian sample - Moretta-Herrera, Rodrigo (2021)
ABSTRACT The aim of the study was to evaluate the construct validity based on the internal structure, the relationship with other variables, and the internal consistency among items of the Fear of COVID-19 Scale (FCV-19S) in a sample of 743 Ecuadorians. The findings confirm the presence of a bifactor structure, which includes a general factor and two specific factors: one emotional and the other physiological. The general factor, and the specific factors presented adequate levels of internal consistency. Finally, the FCV-19S showed a highly significant relationship with GAD-7 at the latent level. The scale has adequate psychometric properties for its application.